Magnetic resonance imaging in five patients with a tumefactive demyelinating lesion in the central nervous system - HELGA C. ALMEIDA SILVA; DAGOBERTO CALLEGARO; PAULO E. MARCHIORI; MILBERTO SCAFF; ANA MARIA C. TSANACLIS (Arquivos de Neuro-Psiquiatria)
Five patients with a tumefactive lesion were clinically followed from 1992 to 1993. Four patients were female; age ranged from 32 to 57 years, the duration of symptoms varied from 3 days to 3 years. Neurological examination disclosed dementia in two patients, aphasia in three, hemiparesis in four, hemihypoaesthesia in three, optical neuritis in two, tetraparesis with sensitive level and neurogenic bladder in one. MRI disclosed lesions with a hypersignal on images assessed at T2 and hyposignal at T1, and gadolinium heterogeneous enhancement; these lesions were located in the: a) temporooccipital region bilaterally and brain stem, b) frontoparietal white matter , c) basal ganglia, bilateral white matter and brain stem, d) left parietal region, e) cervical spinal cord, with enlargement of this region. Cerebral biopsy was performed in three patients; acute and subacute demyelinating disease was diagnosed by histological examination. Two patients had an evolutive diagnosis; exclusion of other pathologies and clinical and radiological improvement after corticotherapy, pointed to an inflammatory disease.